Are low-frequency songs sexually selected, and do they lose their potency in male–female interactions under noisy conditions? (2012)
ABSTRACT: We agree with Halfwerk et al. on the importance of including the receivers when studying the impact of anthropogenic noise. However, we find the conclusion that the use of lowfrequency song is sexually selected in great tits and that noisy conditions affect male–female communication premature for several reasons.